Design of highly sensitive temperature sensor based on photonic band gap structure - Grine, Farouk; Ammari, Halima; Benhabiles, Mohamed Taoufik; Riabi, Mohamed Lahdi (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
In this paper, a novel microstrip resonator technique for temperature sensing is proposed, designed, and implemented using a hybrid planar microstrip line and photonic band gap (PBG) structure. To implement the PBG structure of the microstrip line, a microfluidic channel with periodic form is introduced into the substrate and filled with water. The operation principle of the sensor is based on a frequency shift due to the variation in the center of the band gap, which in turn changes with the variation of the permittivity of water, which relates to the temperature. The different empirical expressions describing the complex permittivity with the resonant frequency were carried out. The proposed sensor is simple in design and low cost, which may be applied in different applications at the industrial.
Optica Applicata, Vol. 54, 2024, nr 1, s. 41-49
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; temperature sensing; photonic band gap structure (PBGS); sensor; microstrip